Existence of Solutions for Elliptic Systems with Nonlocal Terms in One Dimension. (2nd September 2010) - Cabada, Alberto; Cid, J. Ángel; Sanchez, Luís
Abstract : We study the solvability of a system of second-order differential equations with Dirichlet boundary conditions and non-local terms depending upon a parameter. The main tools used are a dual variational method and the topological degree.